The ontogenetic evolution of verbal behavior. Issue 2 (2nd July 2020) - Simon, Carsta
ABSTRACT: Behavior interacts with its environment both during an organism's lifetime and across generations through natural selection. Speech is a natural event that comes down to sounds that affect the behavior of conspecifics. Merging and enhancing Skinner's work on selection as a cause of behavior change on the one hand and his work on verbal behavior on the other provides a theoretical basis for placing verbal behavior in an evolutionary framework. Data suggests that this interaction between behavior and the environment is best described without using the hypothetical concept of response strength. The article proposes a framework that helps us understand selection processes in conversations. After a brief introduction to the value of and the alternative to Skinner's verbal behavior approach, the paper goes on to propose modifications to the conceptualization of verbal operants before concluding with an outline of the possible implications of these modifications for empirical investigations of verbal behavior.